Peningkatan Minat Sastra Melalui Keterampilan Menulis Cerpen di SMPN Satu Atap 4 Purba Sumatera Utara - Ulfah Julianti; Budi Mulia; Desi Karolina Saragih; Bram Denafri (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Learning to write can be started by reading. In addition to reading, the improvement of writing skills is also determined by motivational factors that come from within the writer because writing cannot be separated from activities that are continuously nurtured and developed. For this reason, we from the PKM Team, Sasindo Unpam lecturers, carried out outreach activities with the theme "Increasing Interest in Literature Through Short Story Writing Skills at SMPN Satu Atap 4 Purba SUMUT as a tangible manifestation of lecturers' dedication to the community to devote the Tri Dharma of Higher Education. From a series of short story writing training activities at SMPN Satu Atap 4 Purba SUMUT, the Community Service Team (PKM) of Sasindo Unpam lecturers showed that students of at SMPN Satu Atap 4 Purba SUMUT  were interested in this activity. This is evidenced by the many questions asked by students. After being given an explanation regarding short story writing techniques, the students already know how to write short stories and develop plots and plots in writing short stories.Keywords: short story; writing training; at SMPN Satu Atap 4 Purba SUMUT